Implementation of Islamic Character Education Through Physical Education, Sports, and Health Learning at SDN Winduaji 01 - Izadi, Ifanda Zulfan; Hanif, Muh. (QuranicEdu: Journal of Islamic Education, 2025)
This study aims to analyze the implementation of Islamic character education through learning Physical Education, Sports, and Health (PJOK) at SDN (State Elementary School) Winduaji 01 with Kolb's experiential learning approach. The background is the decline in morality and social ethics of students, which shows that the internalization of Islamic moral values at the elementary school level has not been optimal. This research uses a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed thematically. The results show that Islamic values such as amanah (responsibility), ta'awun (cooperation), shidq (honesty), and tawadhu' (humility) appear naturally in PJOK activities. These values are reinforced through teacher reflection and exemplary behavior. The experiential learning cycle is implemented through four stages: concrete experience, reflection, conceptualization, and active experimentation. However, value reflection and character evaluation have not been systematically implemented. This research shows that experiential learning is effective in shaping holistic Islamic character. Recommendations include the preparation of Islamic value-based lesson plans, affective assessment rubrics, and teacher training. Islamic-based PJOK learning is a strategic solution to form students who are physically healthy and spiritually superior in the context of Merdeka Curriculum and the Pancasila Student Profile.